Bringing Light Into the Dark: Associations of Fire Interest and Fire Setting With the Dark Tetrad - Wehner, Caroline; Ziegler, Matthias; Kirchhof, Simon; Lämmle, Lena (Frontiers in Psychology, 2022)
Fire setting is a significant problem for society, costing many human lives and causing great property damage. One important risk factor of fire setting observed in forensic samples is fire interest. However, little is known about the relations of fire interest and fire setting to other variables such as personality traits in subclinical samples. In the present study we observed the relation of potentially important personality traits with fire interest and fire setting in a sample of N = 222 students. In addition to zero-order correlations we calculated path models and a logistic regression including all predictor variables. From the Dark Tetrad, consisting of psychopathy, narcissism, Machiavellianism, and three facets of sadism, psychopathy and physical sadism were found to be associated with fire interest and fire setting. Furthermore, vicarious sadism was associated with fire interest. The other Dark Tetrad traits as well as four sensation seeking facets did not substantially add to the predictions. This confirms results of previous studies with clinical and forensic samples with psychopathy and sadism as relevant predictors for fire interest and fire setting. Our results also provide evidence for viewing sadism as multidimensional construct discriminating between vicarious and other forms of sadism, for the distinction of psychopathy and Machiavellianism, and for the Dark Tetrad being linked to object related violence.